Remote laboratories extending access to science and engineering curricular - Martyn Cooper (2009)
This paper draws on research, development and deployment of remote laboratories undertaken by the authors since 2000. They jointly worked on the PEARL project [http://iet.open.ac.uk/pearl/] from 2000-2003 and have worked on further projects within their own institutions (the Open University, UK and the University of Porto, Portugal, respectively) since then. The paper begins with a statement of the rationale for remote experiments, then offers a review of past work of the authors and highlights the key lessons for remote labs drawn from this. These lessons include i) The importance of removing accessibility barriers; ii) The importance of a pedagogic strategy; iii) Evaluation of pedagogic effectiveness; iv) The ease of automation or remote control; v) Learning objectives and design decisions. The paper then discusses key topics including assessment issues; instructional design; pedagogical strategies; relations to industry; and cost benefits. A conclusion summarizes key points from the paper within a review of the current status of remote labs in education.